A Novel Perspective Linkage Between Kidney Function and Alzheimer’s Disease - Shi, Yan; Liu, Zhangsuo; Shen, Yong; Zhu, Hanyu (Frontiers in Cellular Neuroscience, 2018)
Abstract It has been long believe that the kidney function links the brain activity. Clinical studies demonstrates that patients with chronic kidney disease (CKD) are more prone to cognitive impairment and Alzheimer’s Disease (AD), and the degree of cognitive impairment is closely related to the CKD progression and renal function failure. Moreover, the fact that the cognitive function in CKD patients was significantly improved after the successful kidney transplantation reveals such linkage between CKD and AD. However, the mechanisms are unclear. Physiological function of the kidney is to maintain the stability of internal environment, included the cerebral vascular circulation whereas abnormal function of the kidney often leads to ischemia and hypoxia. The CKD patients often accompanied with chronic hypoxia and there are many urinary toxins accumulated after renal function impaired. Thus in this mini review, we will propose a novel perspective in association between AD and CKD, and the connection between the kidney and brain.